Rhizobium sp. IRBG74 Alters Arabidopsis Root Development by Affecting Auxin Signaling - Zhao, Catherine Z.; Huang, Jian; Gyaneshwar, Prasad; Zhao, Dazhong (Frontiers in Microbiology, 2018)
Rhizobium sp. IRBG74 not only nodulates Sesbania cannabina but also can enhance rice growth; however, the underlying molecular mechanisms are not clear. Here, we show that Rhizobium sp. IRBG74 colonizes the roots of Arabidopsis thaliana, which leads to inhibition in the growth of main root but enhancement in the formation of lateral roots. The promotion of lateral root formation by Rhizobium sp. IRBG74 in the fls2-1 mutant, which is insensitive to flagellin, is similar to the wild-type plant, while the auxin response deficient mutant tir1-1 is significantly less sensitive to Rhizobium sp. IRBG74 than the wild type in terms of the inhibition of main root elongation and the promotion of lateral root formation. Further transcriptome analysis of Arabidopsis roots inoculated with Rhizobium sp. IRBG74 revealed differential expression of 50 and 211 genes at 24 hours and 48 hours, respectively, and a majority of these genes are involved in auxin signaling. Consistent with the transcriptome analysis results, Rhizobium sp. IRBG74 treatment induces expression of the auxin responsive reporter DR5:GUS in roots. Our results suggest that in Arabidopsis Rhizobium sp. IRBG74 colonizes roots and promotes the lateral root formation likely through modulating auxin signaling. Our work provides insight into the molecular mechanisms of interactions between legume-nodulating rhizobia and non-legume plants.